Cognitive skills you need for the 21st century - Reed, Stephen K. 1944- (Oxford University Press, 2020)
"There is a bookshelf labeled 'Popular Science' in the Geisel Library on the University of California, San Diego campus that provided inspiration for writing this book. I admire those authors who can explain science to a general audience and I continue their tradition in this book on cognitive skills. My objective as a professor emeritus of cognitive psychology is to write a book that does not require specific background knowledge to understand it. I therefore define terms when discussing research and include personal anecdotes that I hope inspire readers to think of related experiences in their own life. I also occasionally include problems to encourage reflection"--